2014
DOI: 10.3109/08820139.2013.857353
|View full text |Cite
|
Sign up to set email alerts
|

In silicoanalysis of potential human T Cell antigens fromMycobacterium tuberculosisfor the development of subunit vaccines against tuberculosis

Abstract: In silico analysis was used to predict MHC class I and class II promiscuous epitopes and potential antigens, from 24 novel T cell antigens of Mycobacterium tuberculosis. Majority of the antigens (16/24) had high affinity peptides to both MHC class I and class II alleles and higher population coverage compared to well-proven T cell antigens ESAT-6, CFP-10 and Ag85B. Among these, highest population coverage were calculated for three novel T cell antigens Rv0733 (97.24%), Rv0462 (96.9%) and Rv2251 (96.3%). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…ESAT-6 and CFP-10 were received as recombinant plasmids from Colorado State University (Fort Collins, Colorado, USA), and the test antigen Lpd (Rv0462) was obtained by in vitro cloning and overexpression [14]. ESAT-6 and CFP-10 were received as recombinant plasmids from Colorado State University (Fort Collins, Colorado, USA), and the test antigen Lpd (Rv0462) was obtained by in vitro cloning and overexpression [14].…”
Section: In Vitro Stimulation Of Whole Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…ESAT-6 and CFP-10 were received as recombinant plasmids from Colorado State University (Fort Collins, Colorado, USA), and the test antigen Lpd (Rv0462) was obtained by in vitro cloning and overexpression [14]. ESAT-6 and CFP-10 were received as recombinant plasmids from Colorado State University (Fort Collins, Colorado, USA), and the test antigen Lpd (Rv0462) was obtained by in vitro cloning and overexpression [14].…”
Section: In Vitro Stimulation Of Whole Bloodmentioning
confidence: 99%
“…The potential of Lpd to induce dendritic cells, a key component in bridging innate and adaptive immune responses toward Th1 polarization, is already proven [13]. However, Lpd-specific T cell profiles were not explicitly analyzed [14]. In silico analysis of T cell antigens from culture filtrate antigens of M. tuberculosis resulted in a higher percentage of class I and class II MHC alleles and higher population coverage by Lpd compared with standard mycobacterial antigens ESAT-6, CFP-10, and Ag85B.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work with H1N1 [ref. 12], Hepatitis B 13 , and Mycobacterial infections 14, 15 has demonstrated the utility of epitope recognition in the development of novel diagnostics and vaccines. Therefore, we propose that detection of a specific lingering cytotoxic T-lymphocyte (CTL) memory response against Zika and/or Dengue, unlike antibody responses, would allow these infections to be distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…18 Other mycobacterial antigens, relevant at different stages of infection, have also been evaluated, such as the combination of Mtb32 (a secreted serine protease) plus Mtb39, termed M72, which in combination with adjuvant AS01 E has shown an acceptable safety profile and induced a potent M72-specific CD4C T cell response in clinical trials performed in adults, even Mtb-infected people, [19][20][21][22] and recently shown to induce robust T cell and antibody responses in HIV-negative adolescents living a TBendemic setting. 23 More recently, approaches to propose new vaccine candidates have been refined by finding T-cell epitopes recognized by individuals suffering from active or latent disease, with bioinformatics being fundamental in predicting new potential targets for the immune system, 24 either from the dominant class of antigens or those that are not as strong as the so called dominant but that still play a relevant role during some part of the interaction with the host critical for establishment of persistence of infection. OMICs technologies (genomics, transcriptomics, proteomics and metabolomics) also start to play a highly prominent role, by making possible to unravel very discrete yet quintessential molecules for M. tuberculosis life cycle that would result in rationally designed vaccine candidates.…”
mentioning
confidence: 99%